Acute Ischaemic Stroke Cooperation Group of Endovascular Treatment (ANGEL) registry: study protocol for a prospective, multicentre registry in China. Issue 1 (19th March 2019) - Huo, Xiaochuan; Ma, Ning; Mo, Dapeng; Gao, Feng; Yang, Ming; Wang, Yilong; Wang, Yongjun; Miao, Zhongrong
Abstract : Background and purpose: Endovascular treatment could improve functional outcomes and reduce mortality in patients with intracranial large artery occlusion. This registry aims to evaluate the endovascular treatment delivery and to improve endovascular treatment algorithm in clinical practice for patients with stroke in China. Methods and analysis: This multicentric, nationwide, prospective registry plans to include 20 stroke centres and recruit 900 consecutive AIS patients with large-artery occlusion under endovascular treatment. This registry will enrol acute large vessel occlusion patients suitable for endovascular treatment and the inclusion and exclusion criteria. In this study, 90 days functional independence (modified Rankin Scale score ≤2) is the primary efficacy endpoint. The procedural efficacy endpoint of this registry is target artery recanalisation defined by modified Thrombolysis in Cerebral Infarction score 2b or 3 after endovascular therapy. Symptomatic intracranial haemorrhage with 24±3 hours after the procedure is the primary safety endpoint of this registry. Ethics and dissemination: Beijing Tiantan Hospital's Ethics committee and all other participating centres approved the protocol and data collection of Acute Ischaemic Stroke Cooperation Group of Endovascular Treatment registry. Each participant or representative had a written informed consent.